Kontektualisasi Visi Sastra Zaman Pra-Islam Dalam Budaya Indonesia Dewasa Ini - Abdul Ghofur (STIT Muslim Asia Afrika, 2019)
This paper discusses the vision of pre-Islamic literature and his ontextualitation in our lives that being lost cultural and value orientation. Literary works are used as study material is the work of Umru al-Qais. The method that used is to describe the elements of literary structure consisting of a theme, the fact the story (plot, characters, and background), and literary devices (point of view, style, atmosphere, symbols, and images). Everything is placed in a sociological framework. It was found that analysis of the poetry of Umru al-Qais legitimize emansipatif literature that has the potential as a force that could bring society to a deeper level to respect the values in society. Although the literature imaginatively constructed, but the framework of his imagination can not be understood out of the empirical frame. With other words, sociological contribution to offer pre-Islamic times, through the work of literary, is imagination.